Star Wars and the History of Transmedia Storytelling - Guynes, Sean A.; Hassler-Forest, Dan (Amsterdam University Press, 2017)
The collection places Star Wars at the center of those studies' projects by examining video games, novels and novelizations, comics, advertising practices, television shows, franchising models, aesthetic and economic decisions, fandom and cultural responses, and other aspects of Star Wars and its world-building in their multiple contexts of production, distribution, and reception. In emphasizing that Star Wars is both a media franchise and a transmedia storyworld, Star Wars and the History of Transmedia Storytelling demonstrates the ways in which transmedia storytelling and the industrial logic of media franchising have developed in concert over the past four decades, as multinational corporations have become the central means for subsidizing, profiting from, and selling modes of immersive storyworlds to global audiences. By taking this dual approach, the book focuses on the interconnected nature of corporate production, fan consumption, and transmedia world-building. As such, this collection grapples with the historical, cultural, aesthetic, and political-economic implications of the relationship between media franchising and transmedia storytelling as they are seen at work in the world's most profitable transmedia franchise.